Residential construction and sedimentation at Kensington, Maryland - Guy, Harold P., author (Colorado State University. Libraries, 1963)
Sediment transported in storm runoff near Kensington, Maryland, during the transformation of part of a 58-acre area from rural to residential land use was measured for 25 storm events from July 1959 to January 1962. These data were used with the water discharge record of nearby Rock Creek in a multiple regression analysis to show the magnitude and trend of sediment movement with time. Total sediment discharged from the area affected by urbanization was 189 tons per acre for the entire period of construction and the subsequent return to a reasonably stable residential area. The high yield of sediment from the Kensington area is attributed to (1) the rolling topography, 3 to 25 percent slope, (2) a very friable soil and subsoil, (3) the construction of a street in the major drainage channel, (4) a tendency for construction methods to expose extensive areas of the soil for a long period of time, and (5) a substantial amount of the 42 inches of annual rainfall occurring at a rate in excess of the infiltration capacity of unprotected soil.
CER63HPG4.
January 28-February 1, 1963.
Keywords: Sediment transport; Sedimentation and deposition